Examination of access and equity by gender, race, and ethnicity in a non-traditional leadership development programme in the United States. Issue 5 (19th October 2016) - Shields, Thomas; Cassada, Kate
ABSTRACT: In developing the next generation of school leadership, school districts across the United States and internationally must consider who is being promoted, the training they are able to access beyond traditional university degree work, the schools in which these emerging leaders enter their first principalships, and how prepared these new leaders are to succeed and remain in the role. This study explores international literature regarding school leader, particularly new leader, development, and placement. The study discusses what is happening internationally in terms of the gender distribution of school leaders and the literature of non-traditional leadership development. To explore gender, race, and ethnicity in hiring and promotion practices, the study employs the methodology of case study analysis. This case study analysis formed from a need to understand the changing dynamics of race, gender, and ethnicity in school leadership in four American school districts participating in a non-traditional regional leadership development programme. These districts, in the Richmond, Virginia (USA) metro area, are experiencing changing student demographics by race, ethnicity, and socio-economic status. Specifically, the study addresses the demographic profile of those seeking leadership, the changing demographics of these communities, and the professional assignment of participating early career leaders.